The role of spontaneous verbal repetition sequences as shared discourse in early linguistic development (Las secuencias de repetición verbal espontánea como formas de discurso compartido en el desarrollo lingüístico temprano). Issue 2 (3rd April 2021) - Casla, Marta; Nieva, Silvia; Murillo, Eva; Moreno, Rebeca; Rodríguez, Jessica; Méndez-Cabezas, Celia
ABSTRACT: Spontaneous verbal repetition is part of early adult–child conversational interchanges. However, most of the studies devoted to verbal repetition analyse child-produced and adult-produced repetition independently. The aim of this study is to analyse verbal repetition sequences that are extended by children and adults participating in turns. We carried out a longitudinal study of 17 parent–child dyads, which included children from the ages of 21 to 30 months. Results show that the frequency of these sequences decreases in the older age range, while the frequency of simple verbal repetitions increases. Participation in repetition sequences is related to the lexical and grammatical development that occurs within the younger ages. Verbal repetition sequences are discussed in terms of their role in early interactions, since they promote attention to the interlocutor and the co-construction of linguistic structures.